Emerging Effects of Sepantronium Bromide (YM155) on MOLT-4 Cell Line Apoptosis Induction and Expression of Critical Genes Involved in Apoptotic Pathways - Shojaei Moghadam, Kobra (Adv Pharm Bull, 2020)
Purpose: Sepantronium bromide (YM155) is a Survivin inhibitor which recently advanced as an anticancer agent in phase II clinical trials. Survivin belongs to IAP (inhibitor of apoptosis) gene family and is a pivotal target for treatment due to its overexpression and oncogenic function in many malignancies, including acute lymphoblastic leukemia (ALL). Although survivin is a specific target for YM155, recent reports have shown that it has many other crucial targets that regulate its anti-apoptotic effects. The aim of this study was to investigate whether YM155 could have an effect on cell death-inducing genes as well as inducing apoptosis in T-ALL MOLT4- cell line. Methods: We treated MOLT-4 cells with increasing concentrations of YM155 and then cell viability was determined using MTT (methyl thiazolyl tetrazolium) assay. Also, the rate of induction of apoptosis in MOLT-4 cells and the target genes expression levels were evaluated by Annexin V/PI and real-time PCR, respectively. Results: YM155 inhibited cell growth in MOLT-4 cells. This outcome is achieved by inducing apoptosis and a significant increase in the expression level of P53, MiR-9, caspase 3 and decreasing the mRNA expression levels of survivin, Sirtuin1(SIRT1), member of anti-apoptotic proteins family (Bcl-2), and epithelial-to-mesenchymal transition (EMT) initiating factors Snail1and Zeb2. Conclusion: The results showed that use of YM155 can be a potential drug therapy in T-ALL patients with promising effects on apoptosis induction.